Games in Tourism Research: Knowledge Structure Mapping and Uncharted Business Perspectives - Hartono, Yudho; Baiquni, Muhammad; Murtiningsih, Siti; Maryono, Agus (Indonesian Business Review, 2026)
In the context of the tourism and hospitality sector, games can enhance experiences and engagement for tourists, contributing to the sustainability of destination. Conversely, the development of digitalization is perceived as accelerating transformations in games designed to address issues ranging from micro to more multifaceted levels. This paper employs bibliometric analysis to investigate the evolution of games in the tourism sector from 2015 to 2025, comparing growth and citation impact. It identifies emerging research topics through cluster and factorial analysis, revealing thematic clusters and conceptual shifts over the past decade by utilising keyword queries in the Scopus database. The investigation utilised VOSviewer and RStudio (Bibliometrix) to examine publications from 2015 to 2025, including countries, funding institutions, authors, and keywords within the specified domain. The study explains the role of funded organizations in facilitating research production, revealing that European countries continue to dominate both paper production and citations. China has the third rank among Asian countries. The study highlights the significance of games in enhancing capacity building and opportunities within the field of tourism. The findings provide a framework for understanding how games could achieve a strategic position not just in micro-scale simulations but also in addressing sustainable challenges within the tourism sector.